Relationship between the Traffic Parameters and Road Traffic Accidents using Fuzzy Logic Designer in Matlab: A Case Study of Uganda’s Road Traffic Accident - Atim, M.R.; Wanzala, J.N.; Anguma, S.K. (International Journal of Artificial Intelligence and Mechatronics, 2021)
Road traffic accidents in Uganda continue to increase with increasing parameters like population, cars owned. The accidents mainly increase due to driver errors. Strictness on the driving lessons in driving schools have been put in place; however, even the experts in driving, keep making errors. Driving while tired or under the influence of alcohol, are some of the reasons why accidents increase. In this study, fuzzy logic has been used to simulate the relationship between the traffic parameters and road traffic accidents. The results have shown that the traffic parameters increase the road traffic accidents. It was simulated that with no parameters in place, a vehicle is at 62 percent chance of moving, that is, 38 percent accident chance in case the driver moves, while with parameters in place; the motion chance reduces to 48.2 percent; that is, 51.8 percent accident chance in case the driver moves.
Keywords: Fuzzy Logic; Traffic Lights; Traffic Parameters; MATLAB